Australian breast surgeons and ultrasound usage: Have practices changed?. Issue 4 (26th June 2021) - Bennett, Ian; Khoo, Jeremy F.; De Viana, Daniel; Law, Michael
Abstract: Background: A recent survey of surgeon performed ultrasound usage was conducted amongst registered members of the Breast Surgeons of Australia and New Zealand Society (BreastSurgANZ) and was compared with a previous survey undertaken in 2010 to determine whether patterns of utilization had changed. Methods: From July to September 2019, members of BreastSurgANZ were invited to complete an electronic online survey of personal usage of breast ultrasound focusing on ultrasound equipment access, use of office and intraoperative ultrasound, biopsy interventions and training expectations. Results: There were 73 respondents to the survey with 45 (61.6%) members indicating access to ultrasound within their practices. Whilst current regular ultrasound usage (68.1%) was only slightly greater than in 2010 (66%), the proportion of respondents not performing any form of needle intervention had increased (62.5% compared to 53% in 2010) and with the proportion of surgeons currently performing >10 biopsies per month decreasing from 10% to only 5.56%. However the percentage of surgeons utilizing intraoperative ultrasound had notably increased since 2010 with 49.3% currently using ultrasound in the operating room compared with only 17% previously. The majority of respondents believed that breast ultrasound training should be conducted through BreastSurgANZ post fellowship training programs. Conclusion: The overall utilization of surgeon‐performed ultrasound amongst BreastSurgANZ members has remained similar over the past 9 years with the performance of needle interventions declining slightly, but with the application of intraoperative ultrasound having increased. An ultrasound training curriculum as part of the BreastSurgANZ post fellowship training program is a necessary imperative.